ผลของเมพิควอทคลอไรด์ คลอร์มีควอทคลอไรด์ และพาโคลบิวทราโซล ต่อสรีรวิทยาการออกดอกของมะม่วงพันธุ์น้ำดอกไม้สีทอง - มะลิวรรณ นาสี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The study on effect of mepiquat chloride, chlormequat chloride, and paclobutrazol on flowering of mango cv. ‘Nam Dok Mai Si Thong’ was carried out during July 2012 to March 2013 at Sansai district, Chiang Mai. The experiment was designed based on Randomized Complete Block Design (RCBD) with 5 treatments and 3 blocks (10 trees each); 1) control, 2) soil drench with paclobutrazol 1 g a.i/m2, 3) foliar spray with mepiquat chloride 3,000 mg/l, 4) foliar spray with chlormequat chloride 1,000 mg/l, and 5) foliar spray with mepiquat chloride 3,000 mg/l mixed with chlormequat chloride 1,000 mg/l. The results showed that all growth retardant could induce flowering of mango trees faster than control, which flowered at 87-92 days after treatments. The treatment of soil drench with paclobutrazol 1 g a.i/m2 gave the highest flowering of 96.16 % whereas foliar spraying with mepiquat chloride 3,000 mg/l and chlormequat chloride 1,000 mg/l and mepiquat chloride 3,000 mg/l plus chlormequat chloride 1,000 mg/l showed lower flowering percentage than paclobutrazol at 65.46-82.13 %. All treatments gave similary flower quality, 67.11-77.54 % of full flower, 22.46-32.89 % of leafy flower. Moreover, paclobutrazol 1 g a.i/m2, mepiquat chloride 3,000 mg/l plus chlormequat chloride 1,000 mg/l and chlormequat chloride 1,000 mg/l bettes more effect on flower number per panicle than mepiquat chloride 3,000 mg/l. Moreover, all foliar spraying treatments promoted higher percentage of fruit setting than using paclobutrazol. For flowering physiology, It was found that soil drench with paclobutrazol 1 g a.i/m2, spraying with mepiquat chloride 3,000 mg/l plus chlormequat chloride 1,000 mg/l induced flowering bud at 45 days after treatment, whereas treatment with mepiquat chloride 3,000 mg/l, chlormequat chloride 1,000 mg/l showed flowering bud at 60 days after treatment. Total nonstructural carbohydrate content reducing sugar and Phosphorus content was increased before flowering, while the control treatment was decreased. Nitrogen content at floral primodium stage was decreased, after that increased before flowering. Potassium content was increased at floral primodium stage and vegetative growth at 15-45 days after treatment.